2017
DOI: 10.1093/jac/dkx395
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the potential of NAI-107 for treating serious ESKAPE pathogens: synergistic combinations against Gram-negatives and bactericidal activity against non-dividing cells

Abstract: ObjectivesTo characterize NAI-107 and related lantibiotics for their in vitro activity against Gram-negative pathogens, alone or in combination with polymyxin, and against non-dividing cells or biofilms of Staphylococcus aureus. NAI-107 was also evaluated for its propensity to select or induce self-resistance in Gram-positive bacteria.MethodsWe used MIC determinations and chequerboard experiments to establish the antibacterial activity of the examined compounds against target microorganisms. Time–kill assays w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 39 publications
2
38
0
Order By: Relevance
“…However, recent work examining the bacteriocin NAI-107 found that this lantibiotic has activity against a small number of fastidious Gram-negative pathogens, and synergizes with polymyxin to inhibit a broader range of Gram-negative pathogens including Klebsiella pneuomoniae , and E. coli . 69 Several groups have also attempted to artificially broaden the range of targets of bacteriocins. 70,71 For example, Nisin that had been complexed to carbon and gold nanoparticles with a net positive charge had increased access to the periplasm of Gram-negative bacteria and antibacterial activity against E. coli and Pseudomonas aeruginosa.…”
Section: Direct Mechanisms Of Colonization Resistancementioning
confidence: 99%
“…However, recent work examining the bacteriocin NAI-107 found that this lantibiotic has activity against a small number of fastidious Gram-negative pathogens, and synergizes with polymyxin to inhibit a broader range of Gram-negative pathogens including Klebsiella pneuomoniae , and E. coli . 69 Several groups have also attempted to artificially broaden the range of targets of bacteriocins. 70,71 For example, Nisin that had been complexed to carbon and gold nanoparticles with a net positive charge had increased access to the periplasm of Gram-negative bacteria and antibacterial activity against E. coli and Pseudomonas aeruginosa.…”
Section: Direct Mechanisms Of Colonization Resistancementioning
confidence: 99%
“…Other interesting compounds include the lantibiotic NAI-107, consisting of 23 amino acyl residues. It has been shown to be very synergistic with polymyxin B against Enterobacteriaceae and A. baumannii [84].…”
Section: Nab741/spr741mentioning
confidence: 99%
“…Upon leader peptide cleavage, the lantibiotic becomes activated and exhibits antimicrobial activity with efficiencies in the low nanomolar to millimolar range. Lantibiotics like NAI-107 or NVB302 are already subjected to pre-clinical trails and might be good candidates in the treatment of multidrug-resistant strains like MRSA or similar Gram-positive strains 57 .…”
Section: Introductionmentioning
confidence: 99%